Freedom And Sanctity Of Contract: Common Law And Syariah – Some Reflections - Hussein, S. Jaffer (Journal of Malaysian and Comparative Law, 2019)
The concept of freedom of contract and sanctity of contract can be traced to the eighteenth and nineteenth centuries when the theories of Natural law and the doctrine of Laissez-faire held sway over human affairs and conduct in England.